Implementasi Nilai-Nilai Hadis dalam Penguatan Kebijakan Disiplin dan Karakter Siswa di MIS Teladan 1 Ujung Kubu - Muhammad As’adurrofik; Dwi Khairunnisa; Hariza Fitriani; Ira Elizah; Jihan Hana Tahira; Nabila Nabila; Nur Dalilah; Nurul Hasanah; Rusydah Rusydah; Ranndy Ndraha; Yudi Syaputra (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to analyze the implementation of hadith values ​​in strengthening disciplinary policies and character building of students at MIS Teladan 1 Ujung Kubu. The hadith of the Prophet Muhammad SAW is used as a normative and pedagogical basis in the formulation of disciplinary policies that are educational, humanistic, and oriented towards fostering noble character. This study uses a descriptive qualitative approach with data collection techniques through direct observation, in-depth interviews with the principal, teachers, and students, and documentation studies of madrasah rules and programs. The results show that the values ​​of hadith are implemented systematically through the habit of time discipline, instilling manners in daily interactions, teachers' exemplary behavior as role models, and strengthening religious activities such as congregational prayer and prayer habits. The hadith-based disciplinary policy has been proven to contribute positively to strengthening student character, especially in aspects of discipline, responsibility, religious attitudes, and social behavior. This study concludes that the integration of hadith values ​​in disciplinary policies is effective in supporting the goals of Islamic education in elementary madrasas.